Pickleworm, Diaphania nitidalis (Stoll) (Insecta: Lepidoptera: Pyralidae) - John L. Capinera (EDIS)
This document is EENY-164, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: October 2000.